In Vitro Biomechanical Comparison of Four Different Ventral Surgical Procedures on the Canine Fourth-Fifth Cervical Vertebral Motion Unit - Hermann, Andreas; Voumard, Benjamin; Waschk, Maja A.; Hettlich, Bianca F.; Forterre, Franck (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Introduction Biomechanical properties of four different ventral surgical procedures at the canine fourth-fifth cervical (C4–C5) vertebral motion unit (VMU) were assessed and compared with the intact C4–C5 VMU.Materials and Methods The third-sixth cervical vertebral column from 24 skeletally mature Beagle cadavers were randomly allocated to four groups (standard ventral slot, slanted slot, inverted cone slot and intervertebral disc fenestration). Standardized tests were performed for each specimen in flexion/extension, lateral bending and axial rotation. The specimens were tested intact and after completion of one of the three slots techniques or fenestration. Pre-testing, cadaver specimens were confirmed to be free of disease by computed tomography (CT) examination. Post-testing, dimensions of slots and fenestration were determined based on a second CT examination.Results All ventral surgical procedures increased range of motion (ROM) at the C4–C5 VMU compared with intact specimens. The only significant difference in the increase in ROM was observed between slanted slot and fenestration in flexion/extension. The standard ventral slot had a significant higher increase in ROM in extension compared with the other three techniques. The slanted slot had a significant lower increase in ROM in flexion.Discussion/Conclusion The described ventral slot techniques have similar biomechanical effects on the canine cervical vertebral column. In contrast to the findings of a previous study, the slanted slot and inverted cone slot do not appear to provide a biomechanical benefit compared with standard ventral slot.
Keywords: biomechanics; range of motion; cervical spine; canine; dog